Influence of oxygen in the development of retinopathy of prematurity - Joziana Pastro; Beatriz Rosana Gonçalves de Oliveira Toso
ABSTRACT Objective: to describe the influence of oxygen in retinopathy of prematurity (ROP) in premature newborns (PTNB) hospitalized in neonatal units of intensive care and undergoing ophthalmological follow-up procedures after hospital discharge. Method: retrospective cohort study, from January 2014 to June 2016, whose data collection totaled 181 charts. Descriptive and inferential statistical analysis. Results: when using oxygen (O2) in 148 PTNB (81.7%), both mask (n=141; 77.9%; p-value <0.001) and the tracheal tube predominated (n=100; 55.25; p-value <0.001) for 15 days in average. The time of use and O2 concentration of the tracheal tube (p-value <0.001), the time of mask use (p-value <0.001) and the time and concentration of O2 of the continuous positive airway pressure (CPAP) (p-value <0.001) were significant to cause ROP in 50 PTNB (11.31%). Conclusion: the oxygen therapy has influenced the development and severity of ROP, indicating the need to adopt protocols for its use.